INCREASING THE LEARNING MOTIVATION OF SMA NEGERI 2 MANDAU STUDENTS THROUGH THE READING GUIDE LEARNING MODEL - mirja, hadian (Perspektif Ilmu Pendidikan, 2022)
The purpose of this research was to increase students’ learning motivation through the Reading Guide learning model. The participants of this investigation were the students of class XI IPA 2 SMAN 2 Mandau. The implementation of this research was carried out in 2 cycles, with the stages of planning, implementing, observing and reflecting. At the Pre Test stage, the students’ motivation level was 59.2% (low category). These results could be seen from the learning motivation questionnaire that had been made. Then after the implementation of the first cycle, the level of student learning motivation rose to 74.16% (medium category), and in the second cycle showed that the student’s learning motivation increased to 82.02%. In addition to this, an increase also occurred in the teacher’s observation sheet. Where in the first cycle obtained 67.85% and in the second cycle of 82.14%. The increase of student motivation was concluded that the application of the Reading Guide learning model could increase student learning motivation. Keywords: Learning motivation, Reading Guide, Teacher, improvement